"The blinding disease": the history of trachoma in Italians between the 19th and 20th centuries: colonial or national blindness? - Martini, Mariano; Riccardi, Niccolò; Simonetti, Omar; Orsini, Davide; Samassa, Francesco; Parodi, Alessandra (Pathogens and global health, 2024)
Trachoma is one of the oldest known causes of blindness in humans and it is caused by the intracellular Gram-negative bacterium Chlamydia trachomatis serovars A, B, Ba and C. Its transmission has historically been related to poorness, overcrowded housing and scarce hygiene. We have traced the history of trachoma in Italy in the 19th and 20th centuries, among people living in Italy, those who immigrated to America and the population in the colonies, with a focus on Libya (1912-1943). Trachoma knowledge and perception in Italy and in its colonies was ambiguous during the 19th and 20th centuries. Trachoma was responsible for a great morbidity on both sides of the Mediterranean, in Italy as well as in Libya. Trachoma is still one of the leading infectious causes of preventable blindness worldwide and it was widespread in Italy and the Italian colonies in the first half of the last century.
Online veröffentlicht: 24. April 2024
Gesehen am 25.09.2024